2022
DOI: 10.1186/s12943-022-01536-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined angiogenesis and PD-1 inhibition for immunomodulatory TNBC: concept exploration and biomarker analysis in the FUTURE-C-Plus trial

Abstract: Background Immune checkpoint inhibitors had a great effect in triple-negative breast cancer (TNBC); however, they benefited only a subset of patients, underscoring the need to co-target alternative pathways and select optimal patients. Herein, we investigated patient subpopulations more likely to benefit from immunotherapy and inform more effective combination regimens for TNBC patients. Methods We conducted exploratory analyses in the FUSCC cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Antiangiogenic therapy and immunotherapy both act on the tumor microenvironment, and previous preclinical studies have shown that immunotherapy combined with anti-angiogenic drugs synergistically inhibit tumor growth and metastasis ( 33 ). Some clinical trials also confirmed the value of antiangiogenic therapy in combination with immunotherapy ( 34 , 35 ). However, the application of anlotinib combined with ICIs in breast cancer has not yet been reported, our present study shows that anlotinib combined with immunotherapy has also achieved good clinical efficacy in metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 84%
“…Antiangiogenic therapy and immunotherapy both act on the tumor microenvironment, and previous preclinical studies have shown that immunotherapy combined with anti-angiogenic drugs synergistically inhibit tumor growth and metastasis ( 33 ). Some clinical trials also confirmed the value of antiangiogenic therapy in combination with immunotherapy ( 34 , 35 ). However, the application of anlotinib combined with ICIs in breast cancer has not yet been reported, our present study shows that anlotinib combined with immunotherapy has also achieved good clinical efficacy in metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 84%
“…The presence of tumor-infiltrating lymphocytes (TILs) is predictive of a better response to immunotherapy and a favorable prognosis in BC (37)(38)(39)(40). CD8+ T-cell infiltration in BC is independently associated with a reduced relative risk of cancer-related death (41), while TNBCs with CD8 positivity have greater possibilities to benefit from immunotherapy (42). These findings correspond to our results of more CD8+ T cells in the TME of pyroptosis subtype A and low-risk group that had higher expression of PD-1 and PD-L1 and better OS.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of biomarkers is important for treatment strategy development. A recently published biomarker analysis study showed that famitinib (an angiogenesis inhibitor) plus camrelizumab and chemotherapy had an impressive clinical benefit in patients with CD8-positive advanced TNBC, with an ORR of 81.3% and a median PFS of 13.6 months, and those with CD8-and PD-L1-positive tumors benefit more from this regimen [30]. However, combining anti-PD-1/PD-L1 antibody with anti-angiogenesis agent showed clinical benefit irrespective of PD-L1 expression in several other tumor types [31][32][33].…”
Section: Discussionmentioning
confidence: 99%